RURAL MUSLIM SOCIAL CONFLICT RESOLUTION MECHANISM: (Study on the Phenomenology of Religiosity, Local Wisdom and Rural Islamic Education) - Akhmad Ghasi Pathollah; Misbahul Munir; Suparjo Adi Suwarno (FORPIM PTKIS ZONA TAPAL KUDA, 2022)
ABSTRACTThis study aims to describe the social segregation conflicts of rural Muslim communities and their resolution mechanisms based on religiosity/religiousness, local wisdom, and rural Islamic education. This study uses a qualitative method with the type of phenomenology. While the data collection instruments use Observation, Documentation, and Depth-Interview. And the data analysis instrument uses data reduction, data presentation, and data heuristics. While the validity of the data test uses triangulation. And the research locus is villages in the Bondowoso-Situbondo area. The results of this study are; 1) Variants of social segregation conflicts that occur in the community are caused by: identity politics, political preferences, socio-religious groups, education level and intensity of awareness of local wisdom values, 2) Rural Muslim communities have conflict resolution mechanisms based on moderate attitudes, thoughts, and actions that are based on traditional religiosity, local wisdom of mutual cooperation and togetherness and also rural Islamic education whose patron is kyai langgar who becomes the central figure or benga-seppo in the social aspect of village society.Keywords : Conflict Resolution, Social Segregation, Rural Muslims, Religiosity, Local Wisdom and Rural Islamic Education.